2019
DOI: 10.1161/jaha.119.012486
|View full text |Cite
|
Sign up to set email alerts
|

Homoarginine Supplementation Prevents Left Ventricular Dilatation and Preserves Systolic Function in a Model of Coronary Artery Disease

Abstract: Background Homoarginine ( hA rg) has been shown to be cardioprotective in a model of ischemic heart failure; however, the mechanism remains unknown. hA rg can inhibit tissue‐nonspecific alkaline phosphatase ( TNAP ), an enzyme that promotes vascular calcification. We hypothesized that hA rg will exert beneficial effects by reducing calcification in a mouse model of coronary artery disease as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 44 publications
2
30
1
Order By: Relevance
“…Reduction TNAP by short hairpin RNA was reported significantly reduced prostate cancer cells migration with lower vimentin expression 29 . Rodionov et al 6 also reported in a mouse model of coronary artery disease that endothelial TNAP overexpression transgenic mice associated with increased myocardial fibrosis. Both were consistent with our results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Reduction TNAP by short hairpin RNA was reported significantly reduced prostate cancer cells migration with lower vimentin expression 29 . Rodionov et al 6 also reported in a mouse model of coronary artery disease that endothelial TNAP overexpression transgenic mice associated with increased myocardial fibrosis. Both were consistent with our results.…”
Section: Discussionmentioning
confidence: 95%
“…Animal experiment observed an upregulation of TNAP in fibrotic heart 4 . Latest studies of TNAP on cardiac fibrosis demonstrated controversial results 5,6 . The effects of TNAP on cardiac fibrosis and its underlying mechanism are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the present study, the previous analysis in skeletal muscle did not include a validation in a second independent cohort. Creatine supplementation completely normalized the metabolic phenotype of AGAT −/− mice (i.e., weight, glucose and lipid metabolism), whereas only hArg supplementation improved post-myocardial infarction heart failure, diabetic kidney damage, systolic function in a model of coronary artery disease and reduced neointimal hyperplasia in balloon-injured rat carotids [15,17,18,29]. Interestingly, hArg normalized a number of cardiac parameters, which are highly calcium-dependent despite unaltered intracellular calcium levels [15,31].…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation with hArg, but not creatine, significantly reduced infarct sizes and improved outcome [9]. In addition to experimental stroke models, hArg supplementation proved protective in murine models of post-myocardial infarction heart failure, diabetic kidney disease, coronary artery disease and balloon-injured carotids [15][16][17][18]. However, data on the underlying molecular mechanisms and signal transduction pathways in the AGAT metabolism is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…First, AGAT-deficient mice are devoid of hArg and revealed increased infarct sizes and an impaired cardiac contractibility, which were normalized upon hArg supplementation [91,102]. Furthermore, hArg supplementation attenuated detrimental effects of diabetic kidney damage, preserved systolic function in a model of coronary artery disease, reduced neointimal hyperplasia in balloon-injured rat carotids and attenuated post-myocardial infarction heart failure [91,[103][104][105][106].…”
Section: Homoarginine As Marker and Target In Cerebrovascular Diseasesmentioning
confidence: 99%